Fatigue in composites : science and technology of the fatigue response of fibre-reinforced plastics - Harris, Bryan, 1935- (CRC Press ; Woodhead, 2003)
This major handbook is the first authoritative survey of current knowledge of fatigue behaviour of composites. It deals in detail with a wide range of problems met by designers in the automotive, marine and structural engineering industries. Compiled from the contributions of some of the best-known researchers in the field, it provides an invaluable, practical and encyclopaedic handbook covering recent developments.